Methodological approach to participatory formulation of agricultural technical assistance plans with territorial approach - Holmes Rodríguez Espinosa; Carlos Julián Ramírez Gómez (Acta Agronómica)
The collective identification of needs and shared decision-making in projects’ formulation for agricultural development is a process that requires the identification of participatory methodologies to promote active and reflective engagement of producers. The aim of this study was to evaluate a methodological approach for participatory formulation of technical assistance plan with territorial approach. Matrix analysis for the identification and prioritization of the most limiting technical assistance factors for milk production was performed and alternative solutions were defined, through participatory workshops with farmers. The results show the advantages of a collective reflection with stakeholders and quantitative tools reducing subjectivity in decision-making, improving participation in their own development and identifying acceptable alternatives to farmers and viable to the municipality in order to improve lack of pasture and forage management, implementation of good agricultural practices GAP and rational use of agrochemicals.